SIGN-SYMBOL Ψ: CULTIVATING PROFESSIONAL IDENTITY AND PROFESSIONALIZATION IN PSYCHOLOGY EDUCATION - Muradyan, Elena; Manukyan, Mariam (Modern Psychology, 2024)
It is considered the possibility of using the sign-symbol Ψ in work with psychology students from the point of view of their familiarization with the profession. The issue of professionalization of the student is touched upon, it is proposed to pay special attention to one of the main “components” of professionalization - professional identity (PI). The matter of student professionalization is addressed, with a suggestion to give notable focus to a primary aspect of this process - professional identity (PI). The discourse revolves around the potential to cultivate this professional identity using a broad educational pedagogical approach. It highlights the significance of creating and putting into action inventive concepts that establish a constructive path for enhancing professional identity among psychology students. The potential capacity for the psychological influence of the professional symbol ψ on a student-psychologist is supported by an "evidence base." The theoretical perspectives of researchers concerning the significance of symbols and signs for individuals, particularly in relation to their impact on the mind and psyche are examined and discussed. The rationale behind using the term sign-symbol in relation to ψ is justified, as there is a potential transformation of a sign into a simbol and vice versa in a student’s perception, depending on his sence of belonginig to the profession. There is a connection at the theoretical level between PI and such a psychological phenomenon as “personal meaning”A study was conducted with psychology students. The structured interview method, as well as the conversation method, is used as the main research method. The purpose of the study was to find out the influence of the process of creating by students their own symbol ψ on their attitude towards ψ in the context of the formation of a sense of belonging to the profession.Thematic tasks were presented, the solution of which made it possible to draw certain conclusions. The study reveals that the process of creating the symbol ψ fosters a sense of belonging to psychology among psychology students. Additionally, it is obseved that the creative act of designing one’s personal ψ contributes to the formation of a sense of satisfaction among psychology students. The influence of the symbol ψ on the formation of PI is confirmed the leading tendency among students to percieve the significance of ψ for psychologists as “identificational” and “ideological” is revealed. The symbol of ψ is considered as a “catalyst’ that initiates the process of PI formation in a psycholoogy student. The use of psychology symbol ψ is suggested to be implemented in a phased work with psychology students at the initial stage of their education. This aims to introduce them to the profession and enhance the effectiveness of the professionalzation process.
Keywords: symbol; sign; sign-symbol ψ; professionalization; professional identity; ownership towards profession